2006
DOI: 10.1088/0022-3727/39/10/016
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent spectroscopy measurements in nanocrystalline praseodymium doped zirconia powders

Abstract: Praseodymium doped zirconia powder (ZrO 2 : (0.53 at%) Pr 3+ ) was prepared by a co-precipitation technique and annealed in air at a temperature T a = 950 • C. The x-ray diffraction pattern shows a nanocrystalline structure composed of 29.6% monoclinic and 70.4% cubic-tetragonal phases. Medium infrared and Raman analysis confirms the monoclinic/cubic-tetragonal crystalline structure and proves the absence of praseodymium aggregates in the material. Photoluminescent spectroscopy over excitations of 457.9 and 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
(18 reference statements)
1
14
0
1
Order By: Relevance
“…For the KSN-Pr, there are four PL bands related to 4f5d-4f 2 transitions of praseodymium (Pr 3 þ ). In this case, they are centered at around 499 nm (green), 616 nm (orange), 702 nm (red), and 813 nm (near-infrared), as a result of 3 P 0 -3 H 4 , 3 P 0 -3 H 6 , 3 P 0 -3 F 3 , and 1 D 2 -2 H 6 transitions, respectively [26][27][28]. PL property of neodymium (Nd 3 þ ) is ascribed to 4f 2 5d 1 -4f 3 transitions from excited to ground state.…”
Section: Resultsmentioning
confidence: 97%
“…For the KSN-Pr, there are four PL bands related to 4f5d-4f 2 transitions of praseodymium (Pr 3 þ ). In this case, they are centered at around 499 nm (green), 616 nm (orange), 702 nm (red), and 813 nm (near-infrared), as a result of 3 P 0 -3 H 4 , 3 P 0 -3 H 6 , 3 P 0 -3 F 3 , and 1 D 2 -2 H 6 transitions, respectively [26][27][28]. PL property of neodymium (Nd 3 þ ) is ascribed to 4f 2 5d 1 -4f 3 transitions from excited to ground state.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, the absorption spectra of Pr-doped ZrO 2 samples display two sets of narrow, weak bands over the ranges 1,350-1,550 and 1,700-1,900 nm, respectively. However, other bands in the 440-610-nm range associated with 4f inter-level electronic transitions in Pr 3+ ion are not distinguished in the spectra trace of our prepared samples [12,13]. In order to assign the observed bands to the electronic transitions yielded by the Pr cation in the available structural sites in the zirconia lattices, some comment on the results previously obtained by different authors is worthwhile.…”
Section: Resultsmentioning
confidence: 60%
“…In order to assign the observed bands to the electronic transitions yielded by the Pr cation in the available structural sites in the zirconia lattices, some comment on the results previously obtained by different authors is worthwhile. Thus, Ramos-Brito et al [12,13] reported the diffuse reflectance spectra for praseodymium-doped zirconia powders as a function of the relative amount of praseodymium with respect to the zirconium in the starting precursors. The diffuse reflectance spectra of these Pr Intensity (a.u.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, luminescence studies can provide important information about intrinsic and impurity defects in pure and doped ZrO 2 [17][18]. The techniques employed to study the optical properties of lanthanide ion-doped ZrO 2 materials include cathodoluminescence [12,[18][19][20], photoluminescence [13][14][15][16][21][22][23][24][25][26][27] and thermoluminescence [12,[28][29][30][31][32] spectroscopies. Light emission from rare-earth ions is mainly due to electric and magnetic dipole optical transitions within the 4f manifolds or involving configurations such as 4f nÀ 1 and 5d [17].…”
Section: Introductionmentioning
confidence: 99%